Capital, Agency and Distinction in Dynamics of Conversion of Economic Functions of Cities: Lessons from Lafayette (US) - Anderson de Souza Sant\u2019Anna; Reed Elliot Nelson; Daniela Martins Diniz (BBR: Brazilian Business Review)
The transition to the digital society attracts the attention of a growing group of scholars who seek to investigate the constraints of this new stage of the productive forces on urban interventions. From this context comes the motivation for this paper, which proposes to analyze findings of an empirical survey of data conducted in the North American city of Lafayette, with the objective of investigating a process of reconversion of its economic functions in the ongoing transition to the digital economy, with significant implications on the composition of the labor market, particularly in the commercial and services sectors. As a result, Lafayette's spatial distribution reflects striking aspects associated with historical, cultural, ethical and socioeconomic configurations. According to Bourdieu's theoretical framework, it also reflects in this way the habitus of the different social groups, as well as the way in which different capitals - economic, social, cultural and symbolic - are mobilized, aiming at the domain of the field.